Extension and its effect on dairy cattle nutrition and productivity in smallholder dairy enterprises in Kiambu District. - Wambugu, M.N. (University of Nairobi, 2001)
A cross-sectional survey covering 63 households (HH) in three administrative locations of Limuru Division in Kiambu District was carried out by means of a structured questionnaire. The three locations with high contact (HCL), medium contact (MCL) and low contact (LCL) of extension respectively, were selected on the basis of their exposure to government extension service. Twenty-one HH stratified by wealth status, (rich [R], medium [M] and poor [P]) were randomly selected from each location. The information gathered included farm/farmer characteristics, dairy herd structure, farmers’ exposure to extension agencies and participation in extension activities, and performance and level of farmers’ knowledge and practice of dairy technologies. The data was subjected to descriptive analysis and analysis of variance to establish the extent to which extension service affected farming practice. Only 32% of the farmers were in contact with the government extension service. Dairy cooperatives and neighbours were the most important sources of information to all the farmers regardless of location and wealth status. HCL and MCL farmers ranked field days first in extension delivery, while LCL farmers did not express a preference. Knowledge of all dairy technologies was low across locations and wealth groups. However, farmers who were exposed to government extension service both knew and practised more technologies than the LCL farmers (p< 0.05), particularly in technologies related to feeding of napier grass and concentrates. Extension contact had a positive effect on uptake of technologies across extension contact groups, regardless of wealth group, implying that there was need for sustained extension farmer contact. The results showed that field days were the best method of information delivery and therefore needed to be enhanced.